EFEKTIVITAS KONSELING POSITIF MENTAL TIME TRAVEL UNTUK MENGURANGI KECEMASAN IBU DALAM MENGHADAPI MENOPAUSE DI WILAYAH KERJA PUSKESMAS JEMBATAN KECIL - Desi Fitriani; Wayterlis Apriani (Poltekkes Kemenkes Medan, 2021)
Menopause is a process of transition from a productive period to a non-productive period. This period affects the psychological aspect, reminding him that he will grow old because his reproductive organs are no longer functioning and worries about other things that may arise accompanying the end of his reproductive period. This study aims to determine the effectiveness of positive mental time travel counseling to reduce maternal anxiety in dealing with menopause in the working area of ??the Small Bridge Public Health Center. This type of research is true experiments with a posttest-only control design approach. The population of this study were all mothers aged 40-50 years. The sample in this study were 96 people, 48 experimental groups and 48 control groups. The sampling technique was accidental sampling where the sample in the study was mothers aged 40-50 years who were in the area of ??the Small Bridge Health Center. The analysis technique taken is the Paired e t-test statistical test. Univariate results, namely the average anxiety of mothers in dealing with menopause in the group given positive mental time travel counseling is 10.19. The average maternal anxiety in dealing with menopause in the group that was not given positive mental time travel counseling was 19.29. The results of the bivariate analysis obtained a p-value of 0.000 <0.005. It was concluded that positive mental time travel counseling was effective in reducing maternal anxiety in dealing with menopause in the working area of ??the Small Bridge Public Health Center. It is hoped that positive mental time travel counseling can be used as an effort to improve psychological conditions for a good quality of life for postmenopausal women.